Pembuatan Kebaya Modern dengan Menerapkan Hiasan Payet di Lamarie Bridal Couture - Kulsum, Umi; Kharnolis, Mein (PT. Riset Press International, 2025)
This study aims to examine the process and final result of creating a modern kebaya embellished with beading. The method used is practice-led research, which consists of four stages: (1) the pre-design stage, involving idea exploration and concept development through sketches; (2) the design stage, involving the creation of fashion designs; (3) the realization stage, including pattern making, sewing, and garment completion; and (4) the presentation stage, where the fashion product is showcased and used as material for article development and publication. The result of this study is a modern kebaya design that applies beading embellishments inspired by the forms and colors of coral reefs, adding aesthetic value to the garment. The combination of traditional elements and a modern design approach demonstrates that kebaya can evolve into a contemporary garment while maintaining its cultural richness. This study is expected to serve as a reference for designers and educators in fashion to develop innovative, artistic, and culturally rooted fashion designs.